Analysis of the Use of Telemedicine Technology in Emergency Services - Amina Intes; Rini Susanti; Xie Guilin; Rini Nuraini; Dito Anurogo (Journal of World Future Medicine, Health and Nursing, 2024)
One of the technological developments in the world of health is Telemedicine technology. Telemedicine technology has become an innovative solution in providing medical services, including in the emergency department. Telemedicine technology is a concept that combines information and communication technology with healthcare, enabling remote interactions between healthcare providers and patients. This study aims to analyze the use of telemedicine technology in emergency services, identify its benefits, and evaluate its impact on the efficiency and quality of patient care. The research method used is a literature study that analyzes scientific articles, research reports, and official documents related to the implementation of telemedicine in the context of emergency services. The research results show that the use of telemedicine technology in emergency services has increased the accessibility of care, accelerated diagnosis and medical intervention, and reduced response time to emergency cases. Telemedicine also facilitates inter-spatial consultations between doctors and medical personnel, enabling faster and more precise decision-making. In some cases, telemedicine has been successful in reducing the number of visits to brick-and-mortar emergency departments, reducing the burden on the health system, and improving the patient experience by providing easier and faster access to medical services. However, challenges faced include the security of patient data, the required technological infrastructure, and unequal access to technology across regions. In conclusion, the use of telemedicine technology in emergency services has great potential to improve the efficiency and quality of patient care, but efforts are needed to overcome technical, regulatory and data security challenges for its implementation to be successful and sustainable.